98.5k views
3 votes
Can someone please help? Thank you!

Can someone please help? Thank you!-example-1
User LCB
by
4.8k points

1 Answer

4 votes

Answer:


(2x(5x+1))/(4x-1)

Explanation:

Given expression:


((4x^3-12x^2)/(4x^2+7x-2))/((2x^2-6x)/(5x^2+11x+2))

Consider the numerator and the denominator separately.

Numerator:


(4x^3-12x^2)/(4x^2+7x-2)\\ \\=(4x^2(x-3))/(4x^2+8x-x-2)\\ \\=(4x^2(x-3))/(4x(x+2)-(x+2))\\ \\=(4x^2(x-3))/((x+2)(4x-1))

Denominator:


(2x^2-6x)/(5x^2+11x+2)\\ \\=(2x(x-3))/(5x^2+10x+x+2)\\ \\=(2x(x-3))/(5x(x+2)+(x+2))\\ \\=(2x(x-3))/((x+2)(5x+1))

The whole expression:


((4x^3-12x^2)/(4x^2+7x-2))/((2x^2-6x)/(5x^2+11x+2))\\ \\ \\=((4x^2(x-3))/((x+2)(4x-1)))/((2x(x-3))/((x+2)(5x+1)))\\ \\ \\=(4x^2(x-3))/((x+2)(4x-1))\cdot ((x+2)(5x+1))/(2x(x-3))\\ \\ \\=(2x(5x+1))/(4x-1)

User Dzoki
by
5.5k points